"Man, development and environment/ edited by R.S. Doria, Avadesh K.Singh [and] Surendra Singh" - "Doria,R.S.(ed.)" (New Delhi, 1990)
The present book consists of selected papers presented in three National Conferences organised in 1993, 1985 and 1989 respectively by Government Post Graduate College Barwani and Nimar Geography Association in Collaboration with UGC, DST, D.E, MPCOST and EPCO and ICSSR. Alongwith the papers by scholars from various disciplines the presidential address on certain epicentral issues of Modern World.
Keywords: Environmental protection